Incidental findings on brain MRI among Chinese at the age of 55–65 years: the Taizhou Imaging Study - Li, Shuyuan (Sci Rep, 2019)
Asymptomatic brain abnormalities are common incidental findings on brain MRI in the elderly population and can be regarded as imaging markers of early stroke and dementia. We initiated the Taizhou Imaging Study (TIS) to examine the prevalence and correlates of incidental findings using brain MRI among an elderly population residing in a rural area of China. A total of 562 individuals, at the age of 55 to 65 years, participated in the TIS study with a response rate of 90%. The prevalence of lacunes, white matter hyperintensity (WMH), cerebral microbleeds (CMB), perivascular space, and intracranial arterial stenosis was 26.69%, 10.68%, 18.51%, 27.76%, and 12.81%, respectively. Age and hypertension were the major correlates of these incidental findings. Per each year increase in age, the risks of WMH and CMB increased by 15% and 14%. Compared to individuals with normal blood pressure, individuals with hypertension had an increased risk of all incidental findings, with the adjusted odds ratios of 2.28 to 5.45. Correlations of age, gender and body mass index with brain gray matter fraction were also observed. The high prevalence of these findings indicates a need of preventative strategy to help prevent future stroke and dementia in this population.